2012
DOI: 10.1002/rcm.6277
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry combined with multidimensional scaling, binary hierarchical cluster tree and selected diagnostic masses improves species identification of Neolithic keratin sequences from furs of the Tyrolean Iceman Oetzi

Abstract: The identification of fur origins from the 5300-year-old Tyrolean Iceman's accoutrement is not yet complete, although definite identification is essential for the socio-cultural context of his epoch. Neither have all potential samples been identified so far, nor there has a consensus been reached on the species identified using the classical methods. Archaeological hair often lacks analyzable hair scale patterns in microscopic analyses and polymer chain reaction (PCR)-based techniques are often inapplicable du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 49 publications
1
49
1
Order By: Relevance
“…Only a limited number of the species-specific peptides identified (Fig. 2 and Table S5 in File S1), were previously reported in literature describing ancient samples [43], [46][49], [63].…”
Section: Resultsmentioning
confidence: 98%
“…Only a limited number of the species-specific peptides identified (Fig. 2 and Table S5 in File S1), were previously reported in literature describing ancient samples [43], [46][49], [63].…”
Section: Resultsmentioning
confidence: 98%
“…MDS has already been used to evaluate data from many disciplines (Shi et al, 2000;Lenz and Foran, 2010;Hollemeyer et al, 2012), including biomarker data (Revill et al, 1992;Zhou et al, 2015). Classical MDS generally uses the Euclidean distance to distinguish data sets, http://dx.doi.org/10.1016/j.orggeochem.2016.09.008 0146-6380/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies were conducted in the 1990s and were designed to molecular analyze samples of grass most likely coming from the shoes and the cape of Ötzi [1], [2]. Later, studies carried out through matrix-assisted laser desorption/ionization time-of-flight mass spectrometric (MALDI-TOF MS) method and microscopy analyzed fur specimens from the accoutrement and detected chamois, brown bear, goat, cattle, canid species, sheep and red deer [3]–[5]. In 2012 Olivieri et al, [6] identified and sequenced mitochondrial DNA (mtDNA) fragments of sheep ( Ovis aries ) from black animal hair shafts recovered from Ötzi's clothes.…”
Section: Introductionmentioning
confidence: 99%